1999
DOI: 10.1046/j.1365-2141.1999.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of M‐CSF and G‐CSF in Kawasaki disease

Abstract: Summary.To examine any role of macrophage colonystimulating factor (M-CSF), in the immune responses in Kawasaki disease (KD), we serially assayed M-CSF and several related cytokines using ELISA. In 10 paediatric patients with KD the level of M-CSF was significantly higher in the acute phase than in the convalescent phase (1476·1 Ϯ 443·6 v 805·0 Ϯ 184·7 U/ml). Higher levels of serum granulocyte colony-stimulating factor (G-CSF) and interleukin-6 were also found in the acute phase. These results suggest that M-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Previous studies have demonstrated that serum G-CSF is moderately increased in acute KD [5,7,13]. The present study builds on these observations by demonstrating that serum G-CSF is significantly higher in acute-phase KD patients who have developed CAL, suggesting that G-CSF may play a role in the pathogenesis of coronary arteritis in KD.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have demonstrated that serum G-CSF is moderately increased in acute KD [5,7,13]. The present study builds on these observations by demonstrating that serum G-CSF is significantly higher in acute-phase KD patients who have developed CAL, suggesting that G-CSF may play a role in the pathogenesis of coronary arteritis in KD.…”
Section: Discussionsupporting
confidence: 68%
“…We have previously reported that increased serum levels of G-CSF are present in the acute phase of KD [5]. The present study investigates whether increased serum levels of G-CSF or other cytokines are correlated with the presence of coronary arteritis in patients with KD.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, many growth factors such as G-CSF (granulocyte colony-stimulating factor), M-CSF (macrophage colony-stimulating factor) [14], VEGF (Vascular endothelial growth factor) [15] in the acute phase of KD, might accelerate the development of lymphoid malignancies [16]. This immunological disorder present in the acute phase of KD may persist for a long period.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper entitled`High serum levels of M-CSF and G-CSF in Kawasaki disease' by Igarashi et al (1999). We wish to draw the attention of the authors to another disease which shares several features in common with Kawasaki disease (KD), at least as far as the role of macrophages, cytokines and cholesterol is concerned.…”
mentioning
confidence: 98%
“…Low cholesterol was found in early stages of the disease (within 30 d of onset of illness) as compared to samples taken 2±16 months after the onset of KD; however, no correlation was found between serum cholesterol and coronary artery abnormalities associated with KD, indicating a lack of permanent changes in cholesterol metabolism (Salo et al, 1991). With the ®nding of elevated M-CSF levels by Igarashi et al (1999) in children with acute-phase KD, another possible mechanism for the development of coronary artery abnormalities may be postulated. These lesions may be secondary to stimulation of monocytes or monocytederived macrophages (MDM) by M-CSF.…”
mentioning
confidence: 99%